1989
DOI: 10.1101/gad.3.9.1288
|View full text |Cite
|
Sign up to set email alerts
|

P-element-mediated enhancer detection: a versatile method to study development in Drosophila.

Abstract: We generated and characterized >500 Drosophila strains that carry single copies of a novel P-element enhancer detector. In the majority of the strains, the p-galactosidase reporter gene in the P-transposon responds to nearby transcriptional regulatory sequences in the genome. A remarkable diversity of spatially and temporally regulated staining patterns is observed in embryos carrying different insertions. We selected numerous strains as markers for different embryonic organs, tissues, and cells. Many of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
304
2
8

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 648 publications
(319 citation statements)
references
References 33 publications
5
304
2
8
Order By: Relevance
“…Six different X-linked pGawB insertions were tested for transposition efficiency and ranged from 9.3% (MS1096) to 84.3% (Mz376.1). In contrast with previous reports (Brand and Perrimon, 1993;Gustafson and Boulianne, 1996), it is possible to achieve high frequency of GAL4 P-element comparable to pLacZ transposons (Bellen et al, 1989;Bier et al, 1989), indicating that the lower frequencies observed previously probably resulted from the genomic location of the starting pGawB insertion rather than a intrinsic feature. The chromosomal location and the effects of the insertion on the viability and the reproductive ability were determined for 468 lines (Table 1).…”
contrasting
confidence: 99%
“…Six different X-linked pGawB insertions were tested for transposition efficiency and ranged from 9.3% (MS1096) to 84.3% (Mz376.1). In contrast with previous reports (Brand and Perrimon, 1993;Gustafson and Boulianne, 1996), it is possible to achieve high frequency of GAL4 P-element comparable to pLacZ transposons (Bellen et al, 1989;Bier et al, 1989), indicating that the lower frequencies observed previously probably resulted from the genomic location of the starting pGawB insertion rather than a intrinsic feature. The chromosomal location and the effects of the insertion on the viability and the reproductive ability were determined for 468 lines (Table 1).…”
contrasting
confidence: 99%
“…This transposon sits in the untranslated exon 4 of brat (Figure 2a), and it carries a bacterial b-galactosidase gene fused to the P-element transposase, under the control of the transposase promoter (Bier et al, 1989). We suspected that this transposon can be utilized as a brat enhancer trap (Bellen et al, 1989;Bier et al, 1989), namely that the b-galactosidase expression mimics brat expression due to the activity of nearby putative brat enhancer elements.…”
Section: Brat Gene Expressionmentioning
confidence: 99%
“…Transcriptional enhancers are often difficult to identify by a simple survey of genomic sequences since their nucleotide sequence are not well conserved and may be located several tens of kilobases from the site of transcription initiation. Enhancer trapping detects chromosomal enhancer elements in situ with minimal perturbations of the genome structure (Bellen et al, 1989;Bier et al, 1989;O'Kane and Gehring, 1987). A database of enhancer trap elements compiling their expression patterns and precise genomic locations should be extremely useful for studies of gene expression and genome analyses.…”
mentioning
confidence: 99%